Local Wisdom, Dignity, Trust, and the Construction of Social Collateral for Micro Financing - Misanam, Munrokhim (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
Micro business plays an important role in poverty alleviation. Yet, its development is constrained by the absence of access to banking at a reasonable cost. This is simply due to the unavailability of collateral to back up the loan/financing. Actually, the lack of physical collateral may be substituted by social collateral that informally exists in society and the micro-business community. Therefore, there has to be an effort to officialize and construct the social collateral in order for the banking industry to admit and accept it as collateral. This work begins with research on the effect of social capital on repayment performance. This is to the extent that the effect of social capital has long been recognized by many economists, even though not formally theorized. Yet, there are ample notions stating that there is a close relationship between those variables. This research was carried out to see in more detail the role of local wisdom, approached from religiosity. This research was accomplished using a survey method, which got primary data directly from the respondents. The ground of research was the Southern Region of Kedu, Central Java, Indonesia. The results suggest that religiosity shares the effect with social dignity as well as trust and they all show to be dominant variables affecting repayment. The implication is it seems better for both the government and banking industry to consider this arrangement a substitute for physical collateral. Moreover, the construction of social collateral is, indeed, in accord with the uncovered fact. Originality/Value: This paper addresses the issue of loan repayment in Islamic micro financing. Because of the unavailability of collateral in small and micro firms to support loans or financing, this study examines the importance of social capital to substitute physical collateral in dealing with repayment performance.